Budget deficits and debt : a global perspective - Shojai, Siamack (Praeger, 1999)
This text evaluates the impact of fiscal imbalances on the economies of industrialized and developing countries. It covers technical issues, economic consequences, and the political economy of budget deficits and government debt.